2009
DOI: 10.1016/j.virol.2009.02.046
|View full text |Cite
|
Sign up to set email alerts
|

The use of Random Homozygous Gene Perturbation to identify novel host-oriented targets for influenza

Abstract: Conventional approaches for therapeutic targeting of viral pathogens have consistently faced obstacles arising from the development of resistant strains and a lack of broad-spectrum application. Influenza represents a particularly problematic therapeutic challenge since high viral mutation rates have often confounded many conventional antivirals. Newly emerging or engineered strains of influenza represent an even greater threat as typified by recent interest in avian subtypes of influenza. Based on the limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 31 publications
1
65
0
Order By: Relevance
“…This suggests that they have a role in limiting influenza A virus replication; thus, silencing their expression or preventing their function with small-molecule chemical inhibitors could be useful in applications where amplification of virus replication is beneficial such as in the propagation of viruses during vaccine production. It also highlighted the breadth of new information obtained from siRNA screens performed during influenza A virus infection, both in the study reported here and in those done by others (24,25,(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 63%
“…This suggests that they have a role in limiting influenza A virus replication; thus, silencing their expression or preventing their function with small-molecule chemical inhibitors could be useful in applications where amplification of virus replication is beneficial such as in the propagation of viruses during vaccine production. It also highlighted the breadth of new information obtained from siRNA screens performed during influenza A virus infection, both in the study reported here and in those done by others (24,25,(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 63%
“…In this study, we have identified STIP1, FKBP5, and ␣-and ␤-tubulin as binding partners of the PB2 protein ( Table 1), suggesting that PB2 might be involved in multimeric complexes with several chaperones and associated proteins. These proteins were also identified in some of the recent genome-wide screening studies as important for the influenza virus life cycle (32,50,56). The association of the influenza virus RNA polymerase and vRNPs with tubulins has been described previously (28,36), and it has been suggested that this interaction maybe involved in the long-distance transport of virus RNPs from the nucleus to the vicinity of the cell membrane, prior to virion formation and budding (28).…”
Section: Discussionmentioning
confidence: 92%
“…CCT also plays a role in viral assembly of hepatitis B virus (35) and initial folding of EBNA-3 nuclear protein of Epstein-Barr virus (31). Interestingly, the CCT complex has not been identified by the recent genome-wide screening studies (2,18,29,32,50,56) as a host factor involved in the influenza virus life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, we identified 171 cellular interactors of the viral transcription/replication machinery. This method complements previous studies that have aimed to identify critical cellular factors that are involved in the virus life cycle, including a number of genome-wide screens (11)(12)(13)(14)(15). Although informative, these genome-wide screens have failed to identify the specific stages of the virus life cycle at which particular cellular factors are critical.…”
mentioning
confidence: 95%